Sosialisasi Pembelajaran Paradigma Baru Dalam Kurikulum Merdeka Melalui Profil Penguatan Pancasila Bagi Guru-Guru SD Negeri 122391 Pematangsiantar - Sibagariang, Susy Alestriani; Sijabat, Osco Parmonangan; Sihombing, Lisbet Novianti; Siahaan, Sanggam Magda Lasmaria; Sirait, Esti; Sitorus, Ester; Panggabean, Eva Saryati (LPPM STIKOM Tunas Bangsa, 2024)
The Socialization Activity of New Paradigm Learning in the Merdeka Curriculum through the Profile of Strengthening Pancasila for Teachers of SD Negeri 122391 Pematangsiantar aims to provide solutions to problems faced by partners, namely the lack of understanding regarding the implementation of the Merdeka Curriculum, especially in designing and compiling Merdeka Curriculum teaching tools at the school level. elementary (SD). The activity was carried out in three stages, namely first 'training/exposing the concept of the Merdeka curriculum for elementary schools which includes a presentation on the design of play activities with reference to Learning Achievements (CP); Explanation of the development of learning pathways and objectives in basic education units based on unit characteristics, children's needs and interests, surrounding environmental conditions, and their relationship to learning outcomes, so that the learning pathways and objectives between each unit can be different; Explanation of developing teaching modules according to students' learning needs. Second, assistance in making learning concept maps for basic education, and third, practice in implementing teaching tools in front of colleagues. The output of this service activity is in the form of increasing understanding of the concepts and methods of implementing the Independent Curriculum for elementary school level. The teachers were very enthusiastic about participating in the training, they responded that with this training they could implement the Merdeka curriculum in their respective schools